Handover technology in high-speed railway broadband wireless communication system - Yunyi LIU; Junhui ZHAO; Chuanyun WANG (Dianxin kexue)
The existing railway mobile communication system can’t meet the requirements of railway information construction.Therefore,the key technology research of next generation of high-speed railway (HSR) communication system needs to be carried out.Handover is a key technology of HSR broadband wireless communication system,which has great significance to ensure the train safety and communication reliability.The research results of the handover in HSR communication system were summarized and the existing problems were investigated.Furthermore,the development directions of handover in the future were explored.